Prognostic Factors in Pediatric Glioma - Imey Pinasty Harianto Putri; I Nyoman Yudayana Indratama; Muhammad Hilmy As Shiddiq; Gantha Narendra Josafat; Bambang Priyanto (Indonesian Publication Center, 2026)
Gliomas are the most common type of central nervous system neoplasms in children, exhibiting distinct clinical and biological characteristics compared to adult gliomas. Pediatric gliomas encompass various histological and molecular subtypes, ranging from low-grade gliomas (LGG) to high-grade gliomas (HGG) and diffuse intrinsic pontine glioma (DIPG), each with differing clinical presentations, treatment responses, and prognoses. This literature review discusses the definition, etiology, epidemiology, pathophysiology, clinical manifestations, diagnostic approaches, treatment modalities, and prognostic factors of pediatric gliomas. Advances in imaging and molecular technologies have enabled more precise diagnostic and therapeutic strategies. Treatment options include surgery, chemotherapy, radiotherapy, and targeted molecular therapies, tailored according to tumor grade and location. A comprehensive understanding of the biological and clinical aspects of pediatric gliomas is essential for improving patient prognosis and quality of life.